Disc Plication as an Operation Method of Temporomandibular Joint Disc Dislocation - V. Machoň; J. Paska (Czech Dental Chamber, 2009)
Authors present their experiences with plication of the disc of the temporomandibular joint. Indications for this surgery method are chronic closed lock (disc dislocation without reduction), when conservative methods are unsuccessful. Good results are in 90 % from patients in this 12 months long term study.